Research on Collaborative Mechanism of data Warehouse in Sharing Platform - Quanhong Sun; Qi Xu (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
With the development of distributed computing technology, there remain some important problems of collaborative control in distributed multi-user data sharing: heterogeneous environment, data consistency and concurrent operation. To solve the sharing issues in drilling engineering, this paper introduces a method of realizing information sharing by combining the advantages of multi-agent collaborative working mechanism and data warehouse technology. Firstly, the structure of multi-agent collaborative working mechanism is put forward based on distributed data warehouse, in which the underlying data layer adopts the distributed data warehouse to organize the information, and the model of that is set up by dimensional modeling technology. Then the information sharing platform and multi-user access controlling method are analyzed, and the collaborative model is put forward. Finally through the multi-agent interaction, the management and sharing of all kinds of information in DDW can be realized. So the application of multi-agent and DDW technology can maximize the value of drilling information and play an important role in improving data sharing degree. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.4411